Dynamics of Changes in Marker of Surgical Stress Cortisol in Transduodenal Endoscopic Surgery Depending on Method of General Anaesthesia - I. I. Titov; S. V. Melnyk; O. L. Tkachuk; V. V. Protas; O. M. Kopchak (Galician Medical Journal, 2016)
There are different types of anaesthetic management of patients undergoing transduodenal endoscopic surgery. However, there is no clear and universally accepted algorithm to choose the method of anaesthesia.